Peran Pembelajaran Jarak Jauh di Masa Pandemi Covid pada Mata Pelajaran Pendidikan Agama Kristen - Deflita Lumi; Irene Presilia Ilat (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to find out, analyze and describe data on the application, barriers and ways to overcome distance learning during the Covid-19 pandemic in Christian Religious Education subjects at SMP N 1 Bontang. This study uses qualitative research using observation, interviews, and documentation methods as data collection techniques that have been carried out at SMP N 1 Bontang. Data collected through observation, interviews, and documentation found that: 1) The application of distance learning during the Covid-19 pandemic was less than optimal, 2) Barriers or obstacles faced by teachers and students, namely there were students who did not have gadgets, limited data quotas, and limited communication between teachers and students 3) Teachers strive to continue to communicate with students and parents and continue to hone competence in order to be skilled in teaching to achieve learning objectives.